ANALYSIS OF SUPERVISION OF SCHOOL OPERATIONAL ASSISTANCE (BOS) FUND MANAGEMENT AT SDI WAE CIU, LAMBA LEDA UTARA DISTRICT, EAST MANGGARAI REGENCY - Roselina Alfera; Apriana H. J. Fanggidae; Siprianus G. Tefa (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study aims to analyze the oversight of the management of School Operational Assistance (BOS) Funds at Wae Ciu Elementary School, Lamba Leda Utara District, East Manggarai Regency, based on Minister of Education and Culture Regulation Number 8 of 2026. The focus of the study covers the five stages of BOS Fund management: planning, implementation, administration, reporting, and accountability, the implementation of internal and external supervision, and the obstacles encountered in overseeing BOS Fund management.This study uses a descriptive qualitative approach with a case study approach. Data sources were obtained through interviews, observation, and documentation. The research informants included the school principal, the BOS treasurer, the school committee, and representatives from the East Manggarai Regency Education Office. Data analysis techniques included data reduction, data presentation, and drawing conclusions, using source and method triangulation to ensure data validity.The research results indicate that the management of the School Operational Assistance (BOS) Fund at SDI Wae Ciu has generally been carried out according to the stages stipulated in Ministerial Regulation Number 8 of 2026. Planning is carried out through the participatory preparation of the School Operational Work Plan (RKAS) involving the principal, treasurer, teachers, and school committee. The implementation and administration of the BOS Fund utilize the ARKAS application and are supported by orderly and complete bookkeeping. Reporting is submitted periodically to the Education Office through a government established system. Internal oversight is carried out by the principal and school committee through document and bookkeeping audits, while external oversight is carried out by the Education Office through monitoring and verification of reports.This research also identified several obstacles in the oversight of BOS Fund management, including the high cost of financing teacher honorariums, limited internet access for using the ARKAS application, and limited human resource capacity in mastering technology. Therefore, increased compliance with regulations, strengthened oversight, and increased capacity of BOS Fund managers are needed to ensure more accountable, transparent, effective, and efficient management of the Fund. Keywords: Supervision, BOS Fund Management, Accountability, Transparency, ARKAS.